Analisis Yuridis Dampak Kepailitan PT Sri Rejeki Isman Tbk terhadap Keberlangsungan Hukum Anak Perusahaan: Analisis Yuridis Dampak Kepailitan PT Sri Rejeki Isman Tbk terhadap Keberlangsungan Hukum Anak Perusahaan: Studi pada PT Primayudha Mandirijaya Boyolali - Irhamnia Irhamnia; Rizky Rahmadhani (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
This study aims to analyze the bankruptcy process of PT Sri Rejeki Isman Tbk (Sritex) according to Law Number 37 of 2004. In addition, the legal impact on its subsidiary, PT Primayudha Mandirijaya in Boyolali, including legal protection for affected employees, will also yang be reviewed. The research method used is normative legal research with a statutory approach and a conceptual approach. Data were obtained through a literature review of relevant regulations and legal literature. The results of the study indicate that although PT Sri Rejeki Isman Tbk has been declared bankrupt by the commercial court, legally, the assets of PT Primayudha Mandirijaya as a subsidiary do not immediately become part of the bankruptcy estate of its parent company. This is based on the principle that the legal entity is independent (separate legal entity) and its responsimerupakan bilities are limited (limited liability), which separates the assets in question from the parent company and the subsidiary, unless there is evidence indicating a guarantee from the company (corporate guarantee). Furthermore, the legal study on labor protection emphasizes that the rights of PT Primayudha Mandirijaya employees need to be legally protected in accordance with national labor regulations and bankruptcy law to mitigate the social and economic impacts in the Boyolali region. The study concludes that the legal existence of the subsidiary remains independent despite the bankruptcy of its parent company. However, it is crucial to prioritize contractual risk reduction and worker rights security during the curator's handling.